Gold target speeds for 2028 Olympics - Kleshnev, V. (BioRow, 2025)
"Gold target times," or the prognostic speed of future regatta winners, is a popular topic among rowers and coaches. Since the race distance for the Los Angeles 2028 Olympics has been shortened to 1500m, the prognostic speed cannot be derived simply by proportionally shortening the target times for the 2000m race. This is because athletes will be able to generate more power and achieve higher speeds in shorter races. The key question to be answered is: "How much faster will a 25% shorter race be compared to the standard 2000m distance?"